High School Size, Achievement Equity, and Cost - Bickel, Robert; Howley, Craig; Williams, Tony; Glascock, Catherine H. (Education Policy Analysis Archives, 2001)
The past decade has occasioned a dramatic increase in research on relationships between school size and a variety of outcomes, including measured achievement, high school completion rates, and postsecondary enrollment rates. An interesting interaction effect which has been found in replications across seven very different states is that as school size increases, the "achievement test score costs" associated with the proportion of economically disadvantaged students enrolled in a school also increase. In short, as schools get larger, average achievement among schools enrolling larger proportions of low socioeconomic-status students suffers. A traditional argument against smaller schools, however, is that they are simply